2011
DOI: 10.1111/j.1753-4887.2011.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and disease risk among aboriginal Arctic populations

Abstract: Aboriginal populations living above the Arctic Circle are at particularly high risk of vitamin D deficiency due to limited ultraviolet B exposure (related to geographic latitude) and inadequate dietary intake (recently related to decreased traditional food consumption). Major changes in diet and lifestyle over the past 50 years in these populations have coincided with increased prevalence rates of rickets, cancer, diabetes, and obesity, each of which may be associated with vitamin D inadequacy. This review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 72 publications
(211 reference statements)
1
63
0
1
Order By: Relevance
“…This is particularly relevant in current times as there have been several reports to date demonstrating lower D-25 levels in Nordic countries and increasing prevalence of rickets, cancer, diabetes, obesity, and morbidities may be associated with D-25 inadequacy [17]. In our study, we observed an increasing D-25 level with increasing age; in other words, older patients had higher D-25 levels than younger patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This is particularly relevant in current times as there have been several reports to date demonstrating lower D-25 levels in Nordic countries and increasing prevalence of rickets, cancer, diabetes, obesity, and morbidities may be associated with D-25 inadequacy [17]. In our study, we observed an increasing D-25 level with increasing age; in other words, older patients had higher D-25 levels than younger patients.…”
Section: Discussionsupporting
confidence: 66%
“…05894913 190, Modular Analytics E170 analyzer; Roche) according to the manufacturer's instructions. Cutoff levels were defined in accordance with the Finnish Current Care Guidelines [16,17]: < 25 nmol/l = severe deficiency; < 50 nmol/l = deficiency; 50-75 nmol/l = sufficient; > 75 = optimal; > 375 = toxic. …”
Section: Serum Vitamin D [25(oh)d] Measurementsmentioning
confidence: 99%
“…The addition of milk and alternatives to TF containing vitamin D [e.g. fatty fish and marine mammals (Health Canada 2010;Sharma et al 2011)] and calcium [e.g. kelp and fish bones (Kim et al 2012)] is essential for children to satisfy their calcium and vitamin D requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Since the studies using murine and rodent osteoblasts indicated that Met might support cellular maturation we extended our studies to an investigation of Met on total ALP expression, a protein absolutely essential for bone collagen calcification [29] and a reliable indicator of osteoblast maturation. Suffice it to say Met, even as high as 10mM, was unable to evoke any increase in total ALP, either alone or in concert with calcitriol, the active metabolite of D3 vital for securing healthy bone tissue formation [30]. On the contrary, Met actually blunted the ability of D3 and an LPA receptor agonist (FHBP) to induce osteoblast maturation, a robust agent pairing in promoting human osteoblast differentiation [31,32].…”
Section: Saj Pharmacy and Pharmacologymentioning
confidence: 99%